Late Cenozoic river reorganization related to tectonic extrusion formed the modern drainage system in southeastern Tibet - Kai Cao; Guocan Wang; T. Mark Harrison; Xiaoping Yuan; Philippe Hervé Leloup; Timothy M. Kusky; Licheng Cao; Xiaoming Shen; Yizhuang Cheng; Junzhe Yao; Xiang He; Zongmin Zhu; et al. (Proceedings of the National Academy of Sciences, 2025)
The formation and organization of southeastern Tibetan river systems reflect feedbacks between tectonics, climate, and landscape evolution. However, our understanding of these interactions remains unclear. We approach this issue from the view that the river incision histories and their bedload provenance provide complementary evidence for reconstructing the evolution of the ancient river system. Zircon and apatite (U-Th)/He data from the middle Jinsha (upper Yangtze) River gorge reveal two episodes of accelerated river incision at 18-17 Ma and 8-7 Ma. The onset of the former incision event, coeval with other incision events along the upper-middle Jinsha and Lancang Rivers, implies their hydrological connection and formation of a south-flowing river system. Additionally, detrital geochronology and thermochronology data of late Oligocene–Miocene fluvial-alluvial sediments along the Red River valley provide constraints on their ages and provenance, suggesting emergence of a throughgoing paleo-Red River in the early-middle Miocene. This ancient Red River was disconnected from the upper Jinsha River but connected with Yalong River (upper Yangtze tributary), forming another south-flowing river system. Landscape evolution modelling supports the view that these south-flowing rivers were successively captured by the westward-propagating Yangtze River in the middle-late Miocene, giving birth to the modern drainages of southeastern Tibet. The resultant integration of the upper-middle and lower Jinsha River is manifested by the progressively upstream-propagating acceleration in river incision from 13-9 Ma to 6-5 Ma along the gorges. Our findings from southeastern Tibet suggest that orogen-scale topographic change, river reorganization, and a coeval increase in biodiversity were driven by extrusion tectonics.